PENGEMBANGAN POTENSI DIRI MELALUI KEGIATAN PENGABDIAN KEPADA MASYARAKAT - Ludfina Laru; Yunis Sulistyorini; Harun Ahmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Potential-Based Community Service (PMBP) is an extracurricular activity that aims to provide services to the community). This is carried out as a form of elaboration in the implementation of the Tri Dharma of Higher Education in which every intellectual candidate not only understands and understands enough about science and technology (IPTEK), but there needs to be a correlation in the level of social life with society in general and more specifically. for people who need the role of students. In the implementation of this Potential-Based Community Service (PMBP) activity, the executor devotes himself to four types of activities, which are carried out in Ciliwung Gang 1 RT 07 RW 11, Purwantoro Village, Blimbing District, Malang City, East Java. The four types of activities are conducting tutoring for early childhood, participating in community organizations in Ciliwung Gang 1 affected by the Covid-19 pandemic, such as providing counseling by spraying disinfectants, social service work, and participating in PKK activities